5.9-p=2

Simple and best practice solution for 5.9-p=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5.9-p=2 equation:


Simplifying
5.9 + -1p = 2

Solving
5.9 + -1p = 2

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-5.9' to each side of the equation.
5.9 + -5.9 + -1p = 2 + -5.9

Combine like terms: 5.9 + -5.9 = 0.0
0.0 + -1p = 2 + -5.9
-1p = 2 + -5.9

Combine like terms: 2 + -5.9 = -3.9
-1p = -3.9

Divide each side by '-1'.
p = 3.9

Simplifying
p = 3.9

See similar equations:

| x-153=55+9x | | 6.3=7.0x | | -4.5(7x-6.5)=-23.5 | | 52-4x=10-10x | | 3x-2(x-3)+4(x+1)=-5 | | 2x-102-10x=42 | | -9(5-5.5k)=26.5 | | 14-8m= | | -77-10x=165+x | | 5ab*3= | | 5r-14=-44 | | 10x-1=6x+10 | | =9xy^2+6xy-5x | | 24+8y-16w= | | 2(7x-13)=16 | | 5x+(x+2)-3(x-4)=35 | | 5x+3+3x=83 | | 2(7x+13)=16 | | 2x-5+12=7(x-2) | | 3x-7=5+6x | | -2d-9.5d=-2.15 | | 8x+28=60 | | -3(-3r-6)=63 | | 8.5x=6y-c | | 6x-12=20x | | x-4(x+1)-2(x+3)=-60 | | 2(3x-6)=20x | | 8.5c+2.5-8c=22.5 | | x^6-44x^3-4x^2+580=0 | | -88-6x-4x=62 | | 30ab+36ac= | | 2y+3=3y-38 |

Equations solver categories